Developing pondok institutions as a religious tourism product - Mohd Fadil Mohd Yusof; Hasnita Buniamin; Ghazali Ahmad; Mazne Ibrahim (2013)
This paper presents a research in progress about the potential of pondok institutions or Islamic religous seminaries to be developed as a spiritual or religious tourism product. It puts forward how traditional religious education providers might be utilised and developed into spiritual tourism product. It analyzes the current status and conditions of these religious seminaries located at various locations in Malaysia. At the same time, it identifies what are the attributes that are able to attract and motivate the tourists to visit the places and contribute the local economic development. In order to explore various attributes of pondok institutions, series of in-depth interviews with the operators is applied. Based on the evidence from six pondok operators in the country, the potential of pondok institutions or islamic religious seminaries to be developed as a spritual tourism product is very promising. All the operators seem to agree to market the product more extensively especially through the internet the reach for more broad audience. However, most of the institutions are still lacking in terms of basic facilities such as accommodatuion, classroom and number of religious teachers.Various important attributes are identified such as having knowledgeable islamic teachers,curricular contents and providing good facilities and services. With the increase numbers of visitors or tourists come to Pondok to learn about islamic religion and searching for a peaceful mind, Pondok institutions may able to expand as a reputable islamic esducation provider